Answer:
Step-by-step explanation:
m =
y -
= m( x -
)
y = mx + b
~~~~~~~~~~~
(4, 5)
( - 6, 15)
m = (15 - 5) / ( - 6 - 4 ) = - 1
y - 5 = ( - 1)( x - 4 )
y =<em> (- 1) </em>x + <em>9</em>
Answer:
y≥0
Step-by-step explanation:
no matter what is written inside it,
|x|≥0
so here
f(x)≥|-x|
so
f(x)≥0
then
y≥0
Step-by-step explanation:
![8 \frac{1}{3} - 5 \frac{1}{2} = \frac{25}{3} - \frac{11}{2} = \frac{50}{6} - \frac{33}{6} = \frac{17}{6} = 2 \frac{5}{6}](https://tex.z-dn.net/?f=8%20%5Cfrac%7B1%7D%7B3%7D%20%20-%205%20%5Cfrac%7B1%7D%7B2%7D%20%20%3D%20%20%5Cfrac%7B25%7D%7B3%7D%20%20-%20%20%5Cfrac%7B11%7D%7B2%7D%20%20%3D%20%20%5Cfrac%7B50%7D%7B6%7D%20%20-%20%20%5Cfrac%7B33%7D%7B6%7D%20%20%3D%20%20%5Cfrac%7B17%7D%7B6%7D%20%20%3D%202%20%5Cfrac%7B5%7D%7B6%7D%20)
Answer:
She pays $566.10
Step-by-step explanation:
The mattress store marks a mattress up 100%. 100% of $225 is 225. We add 225 to 225 and get 510. Therefore, the store sells the mattress for $510 without tax. When Cassie buys the mattress, we have to add 11% tax. We change 11% to 0.11 and multiply that by the selling price (510). We get 56.10, so that is the tax. We add the tax to the selling price and get $566.10. Cassie pays $566.10 for the mattress.
I hope this helped and please mark me as brainliest!